PENERAPAN PPKM SKALA MIKRO DI DESA BEKAT MULYA KECAMATAN SIMPANG EMPAT, KABUPATEN BANJAR - Ellisa Vikalista; Atika Rusli; Muhammad Ihza Anfasa Noor; Indriani; Alisha Qathrunnida (Journal of Empowerment and Community Service (JECSR), 2022)
Corona viruses are a family of viruses that cause mild to severe symptoms. COVID-19 can be transmitted from human to human through coughing/sneezing droplets. People who are most at risk of contracting this disease are people who have close contact with one of the previous COVID-19 sufferers. One of the village government's efforts to prevent the spread of the Covid-19 virus is to restrict mobility. The activity of conveying restrictions on the implementation of micro community activities (PPKM) to the community of Berkat Mulya Village is carried out face-to-face using a collaborative method with several related parties such as the Village Head, Babinsa (Village Trustees), the Army and Police Members. Good policies will never be separated from the role of community participation in carrying out these public policies. Community participation as a driving force for public policy itself. When the policies implemented are in accordance with the wishes of the community, they will carry out activities/orders according to the policy itself.